PSII-10 In vitro simulation of biofilm development and detachment in dairy cow troughs within the first 7 days after cleaning - Hayer, Jason J (J Anim Sci, 2019)
Water is one of the most important factors concerning animal health and welfare. Therefore, an impairment of livestock water quality through biofilm development and detachment in dairy cow troughs represents a serious threat. To gain a better understanding of biofilm development and detachment, this study evaluates influencing factors in vitro. Cattle trough materials were inoculated with two naturally occurring bacterial cultures from different dairy farms. In a latin square design, detachment of a biofilm within a recommended cleaning interval of 7 days was investigated via total viable count (TVC) of the surrounding medium, depending on origin of culture, trough material (polyethylene or stainless steel), water temperature (5°C or 25°C) or nutrient availability (10% or 50% of nutrient broth, Merck KGaSA). At day 7, developed biofilm was investigated for TVC, Enterobacteriaceae spp. and with an adenosine triphosphate (ATP)-rapid test. All treatments were replicated at least 3 times. From the 4th day on, TVC in the surrounding medium increased by 1.5 log(10) cfu/ml on polyethylene at 5°C, suggesting a maturation and detachment of a grown biofilm. Material and temperature affected biofilm detachment (P < 0.05). In temperature treatments with 25°C, TVC reached maximum within 24h, suggesting that biofilm detached earlier. The composition of the grown biofilm was affected by material, temperature, nutrient level, but not by starting culture. Higher Enterobacteriaceae spp. and TVC were observed on polyethylene than on stainless steel and at higher temperatures compared to lower (P < 0.001, respectively). Nutrient level significantly increased Enterobacteriaceae spp. growth. Rapid ATP-test results showed high Pearson correlations with biofilms TVC (r >0.74; P < 0.001) and might be a practical method to check trough hygiene on farms. Based on our in vitro data, cleaning intervals should be less than 4 days even at low temperatures. Nevertheless, more research is needed to verify data in practice.